Modelling vector-borne and other parasitic diseases. Proceedings of a workshop - Perry, Brian D.; Hansen, James (International Laboratory for Research on Animal Diseases, 1994)
Session one of this report highlights ILRAD's research programs and the modelling needs of ILRAD and FAO. Session two deals with vector and helminth population dynamics with particular reference to ticks, tsetse and helminth. Parasite transmission and host parasite interaction are discussed in sessions three and four respectively. These two sessions deal with theileria, trypanosomes and leishmania. Parasite variations and polymorphism is the topic of session five. Session six discusses the effect of disease control programs and session seven reviews modelling systems. The last two sessions deal with the application of modelling, and collection, collation, analysis and dissemination of data on vector-borne and other parasitic diseases.